OFF-grid efficiency evaluation of an inverter dependent on solar PV generator in Iraq - Nasir, Bilal Abdullah; Khaleel, Kutaiba Khalaf; Khalaf, Mohammed Ahmed (International Journal of Applied Power Engineering (IJAPE), 2025)
The solar photovoltaic (PV) inverter weighted efficiency is more precise and favorable as it mainly deems the inverter output power properties when exposed to disparate solar PV irradiance. The European metrical efficiency (?????), presently, is the bulk broadly admissible in inverter efficiency calculation. This is due to, historically, the European countries have been the biggest exporters and spent of solar PV inverters everywhere in the world. The European efficiency (?????) is a concluded metric relying on a standardized European irradiance profile. However, the rendition weightings embedded in this metric may not be fully representative or appropriate for photovoltaic inverters deployed in regions characterized by different climatic conditions, particularly in equatorial and subtropical environments. Accordingly, this study aims to validate the proposed assumption and develop a novel metrical efficiency equation for inverters operating in the Iraqi climate, specifically Baghdad city, relying on the IEC 61683:1999 criterion and the inverter load-duration curve. The proposed formula, validated with field data from an SMA-SB-4000-TL inverter, estimated the energy outcome of a 5.0 kW off-grid SPV system in Baghdad with a 2% deviation from measured values. These results validate the use of η_EURO tailored to Baghdad conditions as a reliable alternative to ????? or ????. This enhances the accuracy of system energy yield estimation, investment return calculations, and payback period assessment for solar PV systems.